Cytomegalovirus-associated haemophagocytic lymphohistiocytosis: a rare cause of febrile neutropenia during cancer chemotherapy. (14th September 2018) - Bergmann, Kristin; Møller, Hanne Elisabeth Højsgaard; Bergmann, Olav Jonas
Abstract : Febrile neutropenia (FN) is a common complication in patients with cancer during treatment with antineoplastic drugs. The initial cause is usually bacterial, and treatment of FN follows well-defined algorithms. We report a case of a 62-year-old patient with chronic lymphocytic leukaemia (CLL), who developed FN, which was unresponsive to both empirical antibacterial and empirical antifungal therapy. Surprisingly, a diagnosis of the life-threatening condition haemophagocytic lymphohistiocytosis (HLH) associated with cytomegalovirus (CMV) infection was made and treated successfully. CMV-associated HLH has not previously been described in patients with CLL treated with rituximab and bendamustine. It is concluded that HLH should be considered in patients with cancer with FN not responding to conventional antibiotic therapy.